Konflik Internal Umat Islam: Antara Warisan Sejarah dan Harapan di Masa Depan - Baihaki, Egi Sukma (FIKRAH, 2018)
The diversities becomes the reason for some of the people to oppress a person or group which different with them. This conflict often occurs in religious life. Even this conditions are occurring in the internal of Muslim too. Sometimes, the existence of various flow, madhab and Islamic organizations make Muslims fragmented and inevitably claim one another. The truth claim and political interests with the power of the mass aggravating the internal conflict. Chide each other, blaming and misleading people or groups become routines that we often encounter. By using a qualitative approach in the form of literature studies (Library Research) we will find that the internal conflicts of Muslims are both historical products and heritage caused by political interests, as well as differences in religious understanding. As long as the ego, political interests, and fanaticism still exist, the differences that exist between Muslims are very difficult to unite. Conflicts can be resolved if there is consensus to respect each other and maintain good relations by promoting a spirit of unity and prioritizing the interests of religion. This research is expected to be an input in designing efforts to resolve internal conflicts of Muslims.